Analytical expressions for noncapillary soil water retention based on popular capillary retention models - Streck, T. (2021)
Recently, Weber et al. proposed a new model for noncapillary retention of soil water without introducing new parameters. The model is based on the integral of any given saturation function for the capillary part in log space. In the original paper, the integration was carried out numerically. Here, we derive analytical solutions for the most popular soil water retention models (van Genuchten, Kosugi, and Brooks–Corey).